Dualisme Identitas Peranakan Arab di Kampung Arab Gresik - Mahzumi, Fikri (Program Studi Filsafat Agama Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2018)
The article attempts to ethnographically describe struggle of identity among the Arabian offspring in Indonesia in the post Reformation Era. As the descendants of the Hadrami migrants who have born in Indonesia, the Arabian offspring deal with two interrelated identities; between their responsibility to preserve the traditions of their ancestors and becoming a wholly recognized citizen of Indonesia. The debate about nationalism among the Arabian-Hadrami people appeared prior to Indonesia?s independence revolution. Anti-colonialism movements in this period had raised solidarity and solidity among the Indonesian people. This situation indubitably urged the Arabian-Hadrami people to reformulate their concept of nationalism. As a part of their nationality commitments, the Arabian Hadrami people have subsequently founded two organizations, i.e. Jamiat Khair (est. 1901) and Jamiyat al-Islah wal-Irsyad al-Arabiyah (est. 1915). In 1934, Abdurrahman Baswedan also founded Persatuan Arab Indonesia, which played pivotal role in cultivating Indonesian nationalism among the Arabian-Hadrami people. In the post Reformation Era, however, the issue of nationalism of the Arabian offspring has never been re-discussed. Employing ethnographical approach this study observes the ways the Arabian offspring, in Kampung Arab (the Arabic Town) in Gresik, compromise and negotiate with two challenges they face at once; as the heirs of Hadrami traditions and as a part of Indonesian citizens.